PAI LEARNING IN INTEGRATED SCHOOLS, ISLAMIC BOARDING SCHOOLS, AND INTERNATIONAL SCHOOLS - Harsing; Rizaldy Alpiansyah; Irfan Alkhotiri (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
This study aims to analyze and compare the learning model of Islamic Religious Education (PAI) in three types of educational institutions, namely Integrated Schools, Islamic Boarding Schools, and International Schools. This study uses a qualitative approach with a descriptive-comparative method, where data is obtained through observation, interviews, and document review. The results of the study show that each type of school has different characteristics and approaches in PAI learning. Integrated Schools emphasizes the integration between the national curriculum and Islamic values, so that the learning process is oriented towards a balance between academic and spiritual aspects. Islamic Boarding School develops a learning model based on the pesantren environment, with a focus on character formation and strengthening the memorization of the Qur'an. Meanwhile, the International School applies a multicultural and global approach, where PAI is taught in a method that is adaptive to the international context. A comparison of the three models shows that the advantages of PAI learning can be achieved by combining the strengths of each system.